2020
DOI: 10.3389/fimmu.2020.00388
|View full text |Cite
|
Sign up to set email alerts
|

IDO and Kynurenine Metabolites in Peripheral and CNS Disorders

Abstract: The importance of the kynurenine pathway in normal immune system function has led to an appreciation of its possible contribution to autoimmune disorders such as rheumatoid arthritis. Indoleamine-2,3-dioxygenase (IDO) activity exerts a protective function, limiting the severity of experimental arthritis, whereas deletion or inhibition exacerbates the symptoms. Other chronic disorder with an inflammatory component, such as atherosclerosis, are also suppressed by IDO activity. It is suggested that this overall a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(100 citation statements)
references
References 235 publications
3
97
0
Order By: Relevance
“…This is synchronous with the binding of IFN-γ-regulated factor-1 (IRF-1) to one or both of the IFN-sensitive response elements (ISREs) [ 6 ]. The second, IFN-independent, mechanism of IDO-1 enzyme activation stems from an interaction between B7 complex found on DCs and cytotoxic T-lymphocyte antigen-4 (CTLA-4) on regulatory T-cells (Treg), and is maintained via transforming growth factor-β (TGF-β) and the non-canonical nuclear factor-κB (NFκB) signaling pathway [ 10 ]. More than a decade ago, Metz et al demonstrated the existence of the indoleamine 2,3-dioxygenase 2 (IDO-2) enzyme, and found its tissue pattern expression similar to that of IDO-1 [ 11 ].…”
Section: The Catabolic Pathway Of Tryptophanmentioning
confidence: 99%
“…This is synchronous with the binding of IFN-γ-regulated factor-1 (IRF-1) to one or both of the IFN-sensitive response elements (ISREs) [ 6 ]. The second, IFN-independent, mechanism of IDO-1 enzyme activation stems from an interaction between B7 complex found on DCs and cytotoxic T-lymphocyte antigen-4 (CTLA-4) on regulatory T-cells (Treg), and is maintained via transforming growth factor-β (TGF-β) and the non-canonical nuclear factor-κB (NFκB) signaling pathway [ 10 ]. More than a decade ago, Metz et al demonstrated the existence of the indoleamine 2,3-dioxygenase 2 (IDO-2) enzyme, and found its tissue pattern expression similar to that of IDO-1 [ 11 ].…”
Section: The Catabolic Pathway Of Tryptophanmentioning
confidence: 99%
“…They found that this ratio was significantly reversed in patients with osteoporosis, as patients showed not only lower baseline levels for 3HAA, but also higher levels of AA compared to control [41]. Some studies suggest that a possible explanation is an inhibition of the enzymatic conversion of AA to 3HAA, thus resulting in lower levels of 3HAA [42]. Another project from the Hordaland Health Study examined the relationship between different Kyn pathway metabolites and BMD.…”
Section: The 3-hydroxyanthranilic Acid To Anthranilic Acid Ratiomentioning
confidence: 99%
“…Additionally, hepatocytes express all enzymes within the Kyn pathway and represent a significant source for downstream kynurenines. Some kynurenines, such as quinolinic acid and kynurenic acid exhibit neuromodulatory properties and have thus been implicated in numerous peripheral and CNS diseases (80,81). De novo synthesis of NAD, an essential co-factor in energy metabolism, represents the last step of the Kyn pathway in some cells, such as hepatocytes and macrophages (50,82).…”
Section: Tryptophan Metabolism In Autoimmunity Host and Microbial Trymentioning
confidence: 99%
“…However, IDO expression was decreased in PBMCs of patients with stable disease compared to HCs, and was more drastically reduced along with the serum Kyn/Trp ratio in response to treatment (127). Moreover, a higher Kyn/Trp ratio was observed in patients with depression (46), likely due to decreased serotonin synthesis, and/or neuromodulatory effects of downstream kyurenines (80,81), which are also perturbed in MS patients (47). Murine models of the disease have also implicated Trp metabolism.…”
Section: Tryptophan Metabolites In Autoimmunitymentioning
confidence: 99%